Foreign investor satisfaction towards services provided by Invest Melaka / Muhammad Akmal Ikhwan Md Saat - Md Saat, Muhammad Akmal Ikhwan (Faculty of Business and Management, 2011)
This is a study on the foreign investor satisfaction towards services provided by Invest Melaka. Foreign investor satisfactions are the most important for the company because the investor can easily made any business with that company. In this study, it will discuss on what the factors that influences the foreign investor satisfaction during the process of service delivery. The target population that suggested for this study is investor who are manufacturer in Batu Berendam Free Trade Zone and the suggested sample size for respondent are 50 respondents. The study is to identify the factors that can influence the foreign investor satisfaction towards services provided by Invest Melaka. There will focus on the communication, service quality and investor orientation. These are lots of suggestions from this study and might be useful for future improvement.